Organosilicone heat-conducting gel, preparation method thereof, heat-conducting material and application
By regulating the molecular weight of the suspension chain and chemical crosslinking points in the thermal gel and optimizing the polymer network structure, the problems of oil seepage and mechanical fatigue in long-term use of thermal gel are solved, and the performance of low-permeability oil and fatigue resistance is achieved, and it is suitable for applications such as optical components.
Patent Information
- Application Number
- CN202510087677.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-11
AI Technical Summary
Existing thermal gels are prone to oil seepage and mechanical fatigue during long-term use, especially under high temperature and multi-field coupling, which leads to the impact of optical performance and limits its application in optical components such as 5G optical modules.
Using a silicone thermal gel, the formulation includes side chain vinyl silicone oil, double-ended hydrogen-containing silicone oil, single-ended hydrogen-containing silicone oil, thermal filler and silane coupling agent, the polymer network structure is optimized to improve fatigue resistance and reduce oil permeability by regulating the molecular weight of the suspension chain and the molecular weight between the chemical crosslinking points.
The low-permeability oil and fatigue resistance of silicone thermal gel are achieved, ensuring its stability and reliability under high temperature and multi-field coupling conditions, and are suitable for applications such as optical components.
Smart Images

Figure CN119799010A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of thermal interface materials, and in particular to a silicone thermally conductive gel and a preparation method thereof, a thermally conductive material and applications thereof. Background Art
[0002] At present, thermal conductive gel, as a thermal interface material, is often used to fill the gap between the heat sink and the heat-generating components (air has a large thermal resistance), thereby forming a good heat conduction path, reducing the thermal resistance between the heat-generating components and the heat sink, and improving the stability and reliability of equipment operation.
[0003] Good toughness and resilience ensure that the material is not prone to fracture and damage when subjected to force, and can be fully restored to its original state, which provides a solid foundation for the material to resist fatigue failure. Existing thermal conductive gels often use excessive low molecular weight vinyl silicone oil or small molecule silane coupling agents such as dodecyl trimethoxysiloxane to optimize their flexibility. However, low molecular weight vinyl silicone oil or small molecule additives are very likely to cause oil seepage. In addition, while optimizing flexibility, low molecular weight vinyl silicone oil is very likely to sacrifice its resilience. During long-term use, the thermal conductive gel is subjected to multi-field coupling such as high temperature and extrusion, and it will have problems of oil seepage and mechanical fatigue. The seeping oil easily forms an oil film on the surface of the optical component, resulting in the optical performance being affected, which will limit its application in optical components such as 5G optical modules. In the actual use environment, factors such as mechanical vibration coupling between electronic components, vibration in the application environment, temperature and other multi-physical field coupling can easily cause damage to the thermal conductive material. Therefore, it is necessary to develop a thermal conductive material with low oil seepage and fatigue resistance. Summary of the invention
[0004] In view of this, the present application provides a silicone thermally conductive gel and a preparation method thereof, a thermally conductive material and an application thereof, aiming to improve the technical problems of existing thermally conductive materials such as oil permeation and poor fatigue resistance.
[0005] In a first aspect, an embodiment of the present application provides a silicone thermally conductive gel, which comprises, by mass, 20 to 120 parts of side chain vinyl silicone oil; 1 to 20 parts of double-ended hydrogenated silicone oil; 2 to 110 parts of single-ended hydrogenated silicone oil; 2000 to 4000 parts of thermally conductive filler and 1 to 10 parts of silane coupling agent; wherein the viscosity of the single-ended hydrogenated silicone oil is 200 mPa.S to 1000 mPa.S, the hydrogen content of the single-ended hydrogenated silicone oil is 0.003% to 0.0098%, and the molecular formula of the silane coupling agent is as shown in the following formula (1):
[0006]
[0007] Among them, 12≤n≤40.
[0008] Optionally, 20≤n≤25; and / or
[0009] The hydrogen content of the single-ended hydrogenated silicone oil is 0.003%-0.008%; and / or
[0010] The mass fraction of the thermally conductive filler in the thermally conductive silicone gel is 3000 parts to 3600 parts; and / or
[0011] The thermally conductive silicone gel further comprises 0.1 to 1 part of a catalyst; and / or
[0012] The organic silicon thermally conductive gel further comprises 0.01 to 0.5 parts of an inhibitor.
[0013] Optionally, the viscosity of the side chain vinyl silicone oil is 30-1000 mPa.S; and / or
[0014] The vinyl content of the side chain vinyl silicone oil is 0.2%-1%; and / or.
[0015] The viscosity of the double-ended hydrogen-containing silicone oil is 100-1000 mPa.S; and / or
[0016] The hydrogen content of the double-ended hydrogen-containing silicone oil is 0.02%-0.08%; and / or
[0017] The average particle size of the thermally conductive filler is 0.1 μm-100 μm; and / or
[0018] The thermally conductive filler is selected from one or more of aluminum oxide, aluminum nitride, zinc oxide, boron nitride and diamond.
[0019] Optionally, the catalyst comprises at least one of chloroplatinic acid, chloroplatinic acid-isopropanol complex, and chloroplatinic acid-divinyltetramethyldisiloxane complex; and / or
[0020] The inhibitor includes at least one of ethynyl cyclohexanol, 2-phenyl-3-butyn-2-ol, 2-methyl-3-butyn-2-ol, 3-methyl-1-ethynyl-3-ol, 3,5-dimethyl-1-ethynyl-3-ol, and 3-methyl-1-dodecyn-3-ol.
[0021] Optionally, the thermally conductive filler includes a first filler, a second filler, a third filler and a fourth filler, the average particle size of the first filler is 85μm-95μm, and the mass fraction of the first filler is 1000 to 1500 parts; the average particle size of the second filler is 10μm-30μm, and the mass fraction of the second filler is 500 to 800 parts; the average particle size of the third filler is 1μm-5μm, and the mass fraction of the third filler is 500 to 800 parts; the average particle size of the fourth filler is 0.1μm-0.5μm, and the mass fraction of the fourth filler is 200 to 400 parts.
[0022] Optionally, the hydrogen content of the single-end hydrogen-containing silicone oil is less than one twenty-seventh of the vinyl content in the side-chain vinyl silicone oil.
[0023] A second aspect of the present application provides a method for preparing a silicone thermally conductive gel, comprising the following steps:
[0024] Mixing side chain vinyl silicone oil, double-terminal hydrogen-containing silicone oil, single-terminal hydrogen-containing silicone oil and a silane coupling agent represented by formula (1) according to a ratio to obtain a mixed silicone oil;
[0025] The heat-conductive filler and the mixed silicone oil are mixed according to a proportion to obtain the heat-conductive silicone gel.
[0026] A third aspect of the present application provides a thermally conductive material, which is prepared by curing the organic silicon thermally conductive gel.
[0027] Optionally, the curing temperature of the organic silicon thermally conductive gel is 100° C. to 150° C., and the curing reaction time is 20 min to 40 min; and / or
[0028] The thermal conductivity of the thermally conductive material is greater than 4.0 W / mK; and / or
[0029] The oil permeability of the thermally conductive material is ≤1%; and / or
[0030] The fatigue toughness of the thermal conductive material is greater than 900 J·m -2 .
[0031] A fourth aspect of the present application provides an optical module, which includes the organic silicon thermally conductive gel or thermally conductive material. That is, the organic silicon thermally conductive gel or thermally conductive material is used in the optical module. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without paying any creative work.
[0033] Figure 1 It is a schematic diagram of the test sample structure for the fatigue toughness test provided in the embodiment of the present application. DETAILED DESCRIPTION
[0034] The experimental examples described in this application are only part of the embodiments of this application, not all of the embodiments. All other embodiments obtained by those skilled in the art without creative work are within the scope of protection of this application. In addition, it should be understood that the specific implementation methods described herein are only used to illustrate and explain this application, and are not used to limit this application.
[0035] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0036] In the description of this application, the term "including" means "including but not limited to." The terms first, second, third, etc. are used merely as labels and do not impose numerical requirements or establish a sequence.
[0037] In this application, "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural.
[0038] In the present application, "at least one" means one or more, and "plurality" means two or more. "One or more", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.
[0039] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.
[0040] As a thermal interface material, thermal conductive gel is often used to fill the gap between the heat sink and the heat-generating components (air has a large thermal resistance), thereby forming a good heat conduction path, reducing the thermal resistance between the heat-generating components and the heat sink, and improving the stability and reliability of equipment operation.
[0041] Good toughness and resilience ensure that the material is not prone to fracture and damage when subjected to force, and can be fully restored to its original state, which provides a solid foundation for the material to resist fatigue failure. Existing thermal conductive gels often use excessive low molecular weight vinyl silicone oil or dodecyl trimethoxysiloxane and other small molecule silane coupling agents to optimize their flexibility. However, low molecular weight vinyl silicone oil or small molecule additives are very likely to cause oil seepage. In addition, low molecular weight vinyl silicone oil and hanging chain structures are very likely to sacrifice their resilience while optimizing flexibility. During long-term use, the thermal conductive gel is subjected to multi-field coupling such as high temperature and extrusion, and it will have problems of oil seepage and mechanical fatigue. When used in optical components, the exuded oil is easy to form an oil film on the surface of the optical component, resulting in the optical performance being affected, which will limit its application in optical components such as 5G optical modules. In the actual use environment, factors such as mechanical vibration coupling between electronic components, vibration in the application environment, temperature and other multi-physical field coupling can easily cause damage to the thermal conductive gel. Therefore, it is necessary to develop a low-penetration oil anti-fatigue thermal conductive gel.
[0042] In view of this, the embodiment of the present application provides a silicone thermally conductive gel, which includes, by mass, 20-120 parts of side chain vinyl silicone oil; 1-20 parts of double-ended hydrogenated silicone oil; 2-110 parts of single-ended hydrogenated silicone oil; 2000-4000 parts of thermally conductive filler and 1-10 parts of silane coupling agent; wherein the viscosity of the single-ended hydrogenated silicone oil is 200mPa.S-1000mPa.S, the hydrogen content of the end-terminated hydrogenated silicone oil is 0.003%-0.0098%, and the molecular formula of the silane coupling agent is as shown in the following formula (1):
[0043]
[0044] Wherein, 12≤n≤40. For example, n may be 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40.
[0045] Exemplarily, the hydrogen content of the single-ended hydrogenated silicone oil is 0.003%, 0.004%, 0.005%, 0.006%, 0.007%, 0.008%, 0.009%, 0.0098% and a range between any two of the above values.
[0046] Exemplarily, the viscosity of the single-ended hydrogen-containing silicone oil is 200mPa.S, 250mPa.S, 300mPa.S, 350mPa.S, 400mPa.S, 450mPa.S, 500mPa.S, 550mPa.S, 600mPa.S, 650mPa.S, 700mPa.S, 750mPa.S, 800mPa.S, 850mPa.S, 900mPa.S, 950mPa.S, 1000mPa.S and the range between any two of the above values. It should be noted that, unless otherwise specified, the viscosity in this application refers to the viscosity at room temperature (25°C). The single-ended hydrogen-containing silicone oil in this application does not belong to the main improvement point, and the single-ended hydrogen-containing silicone oil can be obtained from the market, which is not limited here.
[0047] Exemplarily, the mass fractions of the side chain vinyl silicone oil in the silicone thermally conductive gel are 20 parts, 21 parts, 22 parts, 23 parts, 24 parts, 25 parts, 26 parts, 28 parts, 29 parts, 30 parts, 31 parts, 32 parts, 33 parts, 35 parts, 37 parts, 40 parts, 43 parts, 45 parts, 47 parts, 50 parts, 52 parts, 54 parts, 55 parts, 56 parts, 57 parts, 58 parts, 59 parts, 60 parts, 61 parts, 64 parts, 65 parts, 66 parts, 67 parts, 68 parts, 69 parts, 70 parts, 71 parts, 72 parts, 73 parts, 74 parts, 75 parts, 76 parts, 77 parts, 78 parts, 79 parts, 80 parts, 81 parts, 82 parts, 83 parts, 84 parts, 85 parts, 86 parts, 87 parts, 88 parts, 89 parts, 90 parts, 95 parts, 100 parts, 105 parts, 108 parts, 110 parts, 112 parts, 116 parts, 120 parts and ranges between any two of the above values. Further, the mass fraction of the side chain vinyl silicone oil in the silicone thermally conductive gel is 35 parts to 45 parts.
[0048] Exemplarily, the mass fraction of the double-terminal hydrogen-containing silicone oil in the silicone thermally conductive gel is 1 part, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 9.5 parts, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts, 18 parts, 19 parts, 20 parts and the range between any two of the above values. Further, the mass fraction of the double-terminal hydrogen-containing silicone oil in the silicone thermally conductive gel is 6 parts to 7 parts. Furthermore, the mass fraction of the double-terminal hydrogen-containing silicone oil in the silicone thermally conductive gel is 6 parts to 6.5 parts.
[0049] Exemplarily, the mass fractions of the single-ended hydrogenated silicone oil in the silicone thermally conductive gel are 2 parts, 5 parts, 8 parts, 10 parts, 12 parts, 14 parts, 16 parts, 18 parts, 20 parts, 21 parts, 22 parts, 23 parts, 24 parts, 25 parts, 26 parts, 28 parts, 29 parts, 30 parts, 31 parts, 32 parts, 33 parts, 35 parts, 37 parts, 40 parts, 43 parts, 45 parts, 47 parts, 50 parts, 52 parts, 54 parts, 55 parts, 56 parts, 57 parts, 58 parts , 59 parts, 60 parts, 61 parts, 64 parts, 65 parts, 66 parts, 67 parts, 68 parts, 69 parts, 70 parts, 71 parts, 72 parts, 73 parts, 74 parts, 75 parts, 76 parts, 77 parts, 78 parts, 79 parts, 80 parts, 81 parts, 82 parts, 83 parts, 84 parts, 85 parts, 86 parts, 87 parts, 88 parts, 89 parts, 90 parts, 95 parts, 100 parts, 105 parts, 108 parts, 110 parts and ranges between any two of the above values. Further, the mass fraction of the double-terminal hydrogenated silicone oil in the silicone thermally conductive gel is 50 parts to 90 parts.
[0050] Exemplarily, the mass fraction of the thermally conductive filler in the silicone thermally conductive gel is 2000 parts, 2100 parts, 2200 parts, 2300 parts, 2400 parts, 2500 parts, 2600 parts, 2700 parts, 2800 parts, 2900 parts, 3000 parts, 3100 parts, 3200 parts, 3300 parts, 3400 parts, 3500 parts, 3600 parts, 3700 parts, 3800 parts, 3900 parts, 4000 parts and the range between any two of the above values.
[0051] Illustratively, the mass fraction of the silane coupling agent in the silicone thermally conductive gel is 1 part, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 9.5 parts, 10 parts, and a range between any two of the above values.
[0052] The organic silicone thermally conductive gel provided by the present application includes 20-120 parts of side chain vinyl silicone oil, 1-20 parts of double-ended hydrogenated silicone oil, 1-100 parts of single-ended hydrogenated silicone oil, and 2000-4000 parts of thermally conductive filler. By using silicone oil with lower viscosity as the organic matrix, the thermally conductive filler has a higher proportion in the organic silicone thermally conductive gel, so that the cured organic silicone thermally conductive gel has a higher thermal conductivity.
[0053] In addition, under the premise that the proportion of organic silicone thermal conductive gel is relatively high, the thermal conductive filler of the present application is also coordinated with the silane coupling agent of the structure of formula (1) and the single-ended hydrogen-containing silicone oil with a hydrogen content of 0.003%-0.0098%, so that the material after the organic silicone thermal conductive gel in the present application is cured has both high thermal conductivity and fatigue toughness, and low oil permeability.
[0054] According to the Lake-Tomas model, polymer fatigue refers to the energy required for crack propagation to destroy polymer chains per unit area on the crack plane. For a polymer network composed of multiple molecular chains, its fatigue toughness is the sum of the energy required for the breakage of various types of molecular chains (such as cross-linked chains, hanging chains, etc.) (Γ0 = ∑n i N i 3 / 2 b i U i , where N i is the number of Kuhn monomers per chain, n i is the number of molecular chains per unit volume, b i and U i are the length and fracture energy of the Kuhn monomer on the i-th polymer chain, respectively). Since the index of N in the above formula is 3 / 2 and the index of n is 1, the index of N is greater than the index of n, so N has a greater impact on the fatigue threshold. Starting from the molecular chain structure of the thermal conductive gel, this patent prepares a low permeability oil anti-fatigue high thermal conductive gel by regulating the molecular weight of the hanging chain and the molecular weight of the polymer between the chemical crosslinking points.
[0055] Specifically, the present application adds an appropriate amount of single-ended hydrogenated silicone oil with a hydrogen content of 0.003%-0.0098% to the silicone thermally conductive gel, thereby regulating the molecular weight of the dangling chains in the polymer molecular chain and the molecular weight between adjacent chemical crosslinking points, thereby making the obtained silicone thermally conductive gel have higher fatigue resistance and lower oil permeability. At the same time, in the embodiment of the present application, an appropriate amount of macromolecular silane coupling agent with the structure of formula (1) is added to the silicone thermally conductive gel, which can avoid the "quasi-crosslinking" self-entanglement effect of the silicone resin matrix due to the excessive molecular weight, and the silane coupling agent and the dangling chains can form a more effective interface entanglement effect, which is conducive to further improving the fatigue resistance of the silicone thermally conductive gel after curing, and the addition of macromolecular silane coupling agent to the silicone thermally conductive gel is conducive to further reducing the oil permeability of the cured material.
[0056] In some embodiments of the present application, 20≤n≤25. Within this range, it is beneficial to further improve the fatigue resistance of the cured organic silicon thermal conductive gel material and reduce its oil permeability.
[0057] In some embodiments of the present application, the hydrogen content of the single-ended hydrogen-containing silicone oil is 0.003%-0.008%. For example, the hydrogen content of the single-ended hydrogen-containing silicone oil is 0.005%-0.007%. Within this range, it is beneficial to further improve the fatigue resistance of the material after the organic silicon thermal conductive gel is cured and reduce its oil permeability.
[0058] In some embodiments of the present application, the hydrogen content of the single-ended hydrogenated silicone oil is less than one twenty-seventh of the vinyl content in the side-chain vinyl silicone oil. According to the Lake-Tomas model, the distance between the chemical crosslinking points and the molecular weight of the hanging chain jointly affect the fatigue performance. By making the hydrogen content of the single-ended hydrogenated silicone oil less than one twenty-seventh of the vinyl content in the side-chain vinyl silicone oil, the molecular weight of the single-ended hydrogenated silicone oil will not be much lower than the molecular weight between the two vinyl groups, and thus the single-ended hydrogenated silicone oil in the present application is conducive to further improving the fatigue performance of the material after the organic silicone thermal conductive gel is cured.
[0059] In some embodiments of the present application, the viscosity of the side chain vinyl silicone oil is 30-1000mPa.S, and the vinyl content in the side chain vinyl silicone oil is 0.2%-1%. It should be noted that if the viscosity of the side chain vinyl silicone oil is too high, for example, higher than 1000mPa.S, the viscosity of the prepared composite material is relatively large, affecting the processing performance. If the viscosity of the side chain vinyl silicone oil is too low, for example, lower than 30mPa.S, it may cause an increase in the oil overflow rate. The vinyl content in the side chain vinyl silicone oil is 0.2%-1%, which can be compatible with the molecular weight of the single-ended hydrogen-containing silicone oil in this application, which is beneficial to further improve the fatigue performance of the material after the silicone thermal conductive gel is cured.
[0060] Exemplarily, the viscosity of the side chain vinyl silicone oil is 30mPa.S, 40mPa.S, 50mPa.S, 80mPa.S, 100mPa.S, 150mPa.S, 200mPa.S, 250mPa.S, 300mPa.S, 350mPa.S, 400mPa.S, 450mPa.S, 500mPa.S, 550mPa.S, 600mPa.S, 650mPa.S, 700mPa.S, 750mPa.S, 800mPa.S, 850mPa.S, 900mPa.S, 950mPa.S, 1000mPa.S and a range between any two of the above values.
[0061] Exemplarily, the hydrogen content of the side chain vinyl silicone oil is 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1% and a range between any two of the above values.
[0062] In some embodiments of the present application, the viscosity of the double-ended hydrogen-containing silicone oil is 100-1000 mPa.S, and the hydrogen content in the double-ended hydrogen-containing silicone oil is 0.02%-0.08%. It should be noted that if the viscosity of the double-ended hydrogen-containing silicone oil is too high, for example, higher than 1000 mPa.S, the viscosity of the prepared composite material is relatively large, affecting the processing performance. If the viscosity of the double-ended hydrogen-containing silicone oil is too low, for example, lower than 100 mPa.S, it may cause an increase in the oil spill rate.
[0063] Exemplarily, the viscosity of the double-ended hydrogen-containing silicone oil is 100mPa.S, 150mPa.S, 200mPa.S, 250mPa.S, 300mPa.S, 350mPa.S, 400mPa.S, 450mPa.S, 500mPa.S, 550mPa.S, 600mPa.S, 650mPa.S, 700mPa.S, 750mPa.S, 800mPa.S, 850mPa.S, 900mPa.S, 950mPa.S, 1000mPa.S and a range between any two of the above values.
[0064] Exemplarily, the hydrogen content of the double-ended hydrogen-containing silicone oil is 0.002%, 0.003%, 0.004%, 0.005%, 0.006%, 0.007%, 0.008% and a range between any two of the above values.
[0065] In some embodiments of the present application, the resin matrix of the organic silicone thermal conductive gel is composed of side chain vinyl silicone oil, double-terminal hydrogen-containing silicone oil and single-terminal hydrogen-containing silicone oil.
[0066] In some embodiments of the present application, the silicone thermally conductive gel further comprises 0.1 to 1 part of a catalyst. Exemplarily, the catalyst comprises at least one of chloroplatinic acid, chloroplatinic acid-isopropanol complex, and chloroplatinic acid-divinyltetramethyldisiloxane complex.
[0067] In some embodiments of the present application, the silicone thermally conductive gel further comprises 0.01 to 0.5 parts of an inhibitor. Exemplarily, the inhibitor comprises at least one of ethynyl cyclohexanol, 2-phenyl-3-butyn-2-ol, 2-methyl-3-butynyl-2-ol, 3-methyl-1-ethynyl-3-ol, 3,5-dimethyl-1-ethynyl-3-ol, and 3-methyl-1-dodecyn-3-ol.
[0068] In some embodiments of the present application, the mass fraction of the thermally conductive filler in the thermally conductive silicone gel is 3000 to 3600 parts, and further, the mass fraction of the thermally conductive filler in the thermally conductive silicone gel is 3100 to 3300 parts. This is conducive to further improving the thermal conductivity of the material after the thermally conductive silicone gel is cured, and the thermally conductive silicone gel in the present application has better processability.
[0069] In some embodiments of the present application, the average particle size of the thermal conductive filler is 0.1 μm-100 μm. For example, 0.1 μm, 0.2 μm, 0.5 μm, 0.8 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, 5.5 μm, 6 μm, 8 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 18 μm, 20 μm, 21 μm, 22 μm, 23 μm, 24 μm, 25 μm, 26 μm, 28 μm, 29 μm, 30 μm, 31 μm, 32 μm, 33 μm, 35 μm, 37 μm, 40 μm, 43 μm, 45 μm , 47μm, 50μm, 52μm, 54μm, 55μm, 56μm, 57μm, 58μm, 59μm, 60μm, 61μm, 64μm, 65μm, 66μm, 67μm, 68μm, 69μm, 70μm, 71μm, 72μm, 73μm, 74μm, 75μm, 76μm, 77μm, 78μm, 79μm, 80μm, 81μm, 82μm, 83μm, 84μm, 85μm, 86μm, 87μm, 88μm, 89μm, 90μm, 95μm, 100μm and values between any two of the above values. Exemplarily, the average particle size of the thermally conductive filler can be measured by a particle size analyzer.
[0070] In some embodiments of the present application, the mass fraction of the thermally conductive filler in the organic silicone thermally conductive gel is 3000 to 3600 parts, and the thermally conductive filler includes a first filler, a second filler, a third filler and a fourth filler, the average particle size of the first filler is 85μm to 95μm, and the mass fraction of the first filler is 1000 to 1500 parts; the average particle size of the second filler is 10μm to 30μm, and the mass fraction of the second filler is 500 to 800 parts; the average particle size of the third filler is 1μm to 5μm, and the mass fraction of the third filler is 500 to 800 parts; the average particle size of the fourth filler is 0.1μm to 0.5μm, and the mass fraction of the fourth filler is 200 to 400 parts. In this way, it is beneficial to further improve the thermal conductivity and fatigue toughness of the material after the organic silicone thermally conductive gel is cured.
[0071] In some embodiments of the present application, the thermally conductive filler includes an inorganic filler. Specifically, the first filler, the second filler, the third filler, and the fourth filler are independently selected from one or more of aluminum oxide, aluminum nitride, zinc oxide, boron nitride, and diamond. This is conducive to further improving the thermal conductivity of the material after the organic silicone thermally conductive gel is cured.
[0072] Specifically, the first filler is spherical aluminum oxide, and the average particle size of the first filler is 90 μm, the second filler is spherical aluminum oxide, and the average particle size of the second filler is 20 μm, the third filler is spherical aluminum oxide, and the average particle size of the third filler is 2 μm, and the fourth filler is spherical zinc oxide, and the average particle size of the fourth filler is 0.3 μm. Of course, in other embodiments of the present application, the first filler, the second filler, the third filler, and the fourth filler may also be other materials or shapes, which are not limited here.
[0073] The embodiment of the present application also provides a method for preparing a silicone thermally conductive gel, comprising the following steps: mixing side chain vinyl silicone oil, double-ended hydrogen-containing silicone oil, single-ended hydrogen-containing silicone oil, a silane coupling agent represented by formula (1) and a thermally conductive filler according to a ratio to obtain the silicone thermally conductive gel.
[0074] In some embodiments of the present application, the step of mixing side chain vinyl silicone oil, double-terminal hydrogen-containing silicone oil, single-terminal hydrogen-containing silicone oil, silane coupling agent represented by formula (1) and thermal conductive filler according to a ratio to obtain the silicone thermal conductive gel comprises:
[0075] S10: side chain vinyl silicone oil, double-end hydrogen-containing silicone oil, single-end hydrogen-containing silicone oil and a silane coupling agent represented by formula (1) are mixed according to a ratio to obtain a mixed silicone oil.
[0076] It should be noted that the side chain vinyl silicone oil, the double-ended hydrogen-containing silicone oil, the single-ended hydrogen-containing silicone oil, the silane coupling agent and their proportions have been specifically described above and will not be repeated here.
[0077] Specifically, the organic silicone thermal conductive gel also includes an inhibitor. Side chain vinyl silicone oil, double-end hydrogen silicone oil, single-end hydrogen silicone oil, inhibitor and silane coupling agent are added into a container and ultrasonicated at 25° C. for 0.1 to 1 h to obtain mixed silicone oil.
[0078] S20: mixing the thermal conductive filler and the mixed silicone oil according to a proportion to obtain the thermal conductive silicone gel.
[0079] It should be noted that the composition and proportion of the thermally conductive filler have been specifically described above and will not be repeated here.
[0080] Specifically, the silicone thermally conductive gel further includes a catalyst. A preset ratio of mixed silicone oil and thermally conductive filler is added to a planetary mixer, and stirred and blended for 0.5h-3.0h in a vacuum environment to obtain a composite slurry. The composite slurry is cooled to room temperature, and then a catalyst is added to the composite slurry, and stirred for 0.5h in a vacuum environment to obtain the silicone thermally conductive gel.
[0081] Exemplarily, the silicone thermally conductive gel is stored at a low temperature (-15° C. to 10° C.) after being canned.
[0082] The present application also provides a thermally conductive material, which is formed by curing the aforementioned thermally conductive silicone gel or the thermally conductive silicone gel prepared by the method for preparing the thermally conductive silicone gel. Exemplarily, the thermally conductive material is prepared by curing the aforementioned thermally conductive silicone gel at 100° C. to 150° C. for 20 min to 40 min.
[0083] In some embodiments of the present application, the thermal conductivity of the thermally conductive material is greater than 4.0 W / mK. Furthermore, the thermal conductivity of the thermally conductive material is greater than 7 W / mK.
[0084] In some embodiments of the present application, the oil permeability of the thermally conductive material is ≤1%.
[0085] In some embodiments of the present application, the fatigue toughness of the thermally conductive material is greater than 900 J·m -2 .
[0086] In some embodiments of the present application, the thermal conductivity of the thermally conductive material is greater than 7W / mK, the oil permeability of the thermally conductive material is ≤1%, and the fatigue toughness of the thermally conductive material is greater than 900J·m -2 .
[0087] Example 1
[0088] (1) Preparation of silicone thermally conductive gel
[0089] Side chain vinyl silicone oil (40 g) with a viscosity of 30-1000 mPa.S and a vinyl content of 0.5%, double-end hydrogenated silicone oil (6.32 g) with a viscosity of 100-1000 mPa.S and a hydrogen content of 0.04%, single-end hydrogenated silicone oil (84.67 g) with a viscosity of 200-1000 mPa.S and a hydrogen content of 0.006%, macromolecular silane coupling agent (2.62 g, n is 23) represented by formula (1), aluminum oxide (1425 g) with a particle size of 90 μm, aluminum oxide (712.5 g) with a particle size of 20 μm, aluminum oxide (712.5 g) with a particle size of 2 μm, zinc oxide (356.6 g) with a particle size of 0.3 μm, ethynyl cyclohexanol (0.02 g) and a 2.0 L double planetary mixer were added. The mixture was heated to 100°C and stirred at a speed of 50 rpm for 2.0 h to obtain a mixture. The mixture was then cooled to room temperature, and then 0.4 g of chloroplatinic acid-divinyltetramethyldisiloxane complex was added, and the mixture was stirred at 50 rpm for 1.0 h at 20° C. and vacuum degree of -90.0 kPa to prepare a silicone thermal conductive gel.
[0090] (2) Preparation of thermal conductive materials
[0091] The prepared thermally conductive gel was pressed into a sheet of a certain thickness and cured at 100° C. for 30 min to obtain a thermally conductive gasket for testing.
[0092] Example 2
[0093] (1) Preparation of silicone thermally conductive gel
[0094] Side chain vinyl silicone oil (40 g) with a viscosity of 30-1000 mPa.S and a vinyl content of 0.5%, double-end hydrogenated silicone oil (6.32 g) with a viscosity of 100-1000 mPa.S and a hydrogen content of 0.04%, single-end hydrogenated silicone oil (50.8 g) with a viscosity of 200-1000 mPa.S and a hydrogen content of 0.0098%, macromolecular silane coupling agent (1.94 g, n is 23) represented by formula (1), aluminum oxide (1088 g) with a particle size of 90 μm, aluminum oxide (544 g) with a particle size of 20 μm, aluminum oxide (544 g) with a particle size of 2 μm, zinc oxide (300.6 g) with a particle size of 0.3 μm, ethynyl cyclohexanol (0.02 g) and a 2.0 L double planetary mixer were added. The mixture was heated to 100°C and stirred at a speed of 50 rpm for 2.0 h to obtain a mixture. The mixture was then cooled to room temperature, and then chloroplatinic acid-divinyltetramethyldisiloxane complex (0.3 g) was added, and the mixture was stirred at 50 rpm for 1.0 h at 20° C. and vacuum degree-90.0 kPa to prepare a silicone thermal conductive gel.
[0095] (2) Preparation of thermal conductive materials
[0096] The prepared thermally conductive gel was pressed into a sheet of a certain thickness and cured at 100° C. for 30 min to obtain a thermally conductive gasket for testing.
[0097] Example 3
[0098] (1) Preparation of silicone thermally conductive gel
[0099] Side chain vinyl silicone oil (40 g) with a viscosity of 30-1000 mPa.S and a vinyl content of 0.5%, double-end hydrogenated silicone oil (6.32 g) with a viscosity of 100-1000 mPa.S and a hydrogen content of 0.04%, single-end hydrogenated silicone oil (84.67 g) with a viscosity of 200-1000 mPa.S and a hydrogen content of 0.006%, macromolecular silane coupling agent (2.62 g, n is 23) represented by formula (1), aluminum oxide (1425 g) with a particle size of 90 μm, aluminum oxide (712.5 g) with a particle size of 20 μm, aluminum oxide (712.5 g) with a particle size of 2 μm, zinc oxide (356.6 g) with a particle size of 0.3 μm, ethynyl cyclohexanol (0.02 g) and a 2.0 L double planetary mixer were added. The mixture was heated to 100°C and stirred at a speed of 50 rpm for 2.0 h to obtain a mixture. The mixture was then cooled to room temperature, and then 0.4 g of chloroplatinic acid-divinyltetramethyldisiloxane complex was added, and the mixture was stirred at 50 rpm for 1.0 h at 20° C. and vacuum degree of -90.0 kPa to prepare a silicone thermal conductive gel.
[0100] (2) Preparation of thermal conductive materials
[0101] The prepared thermally conductive gel was pressed into a sheet of a certain thickness and cured at 100° C. for 30 min to obtain a thermally conductive gasket for testing.
[0102] Example 4
[0103] (1) Preparation of silicone thermally conductive gel
[0104] Add side chain vinyl silicone oil (24.3 g) with a viscosity of 30-1000 mPa.S and a vinyl content of 0.5%, double-end hydrogenated silicone oil (3.84 g) with a viscosity of 100-1000 mPa.S and a hydrogen content of 0.04%, single-end hydrogenated silicone oil (84.67 g) with a viscosity of 200-1000 mPa.S and a hydrogen content of 0.006%, a macromolecular silane coupling agent represented by formula (1) (2.62 g, n is 39), aluminum oxide with a particle size of 90 μm (1425 g), aluminum oxide with a particle size of 20 μm (712.5 g), aluminum oxide with a particle size of 2 μm (712.5 g), zinc oxide with a particle size of 0.3 μm (356.6 g), ethynyl cyclohexanol (0.02 g) and a 2.0 L double planetary mixer. The mixture was heated to 100°C and stirred at 50 rpm for 2.0 h to obtain a mixture. The mixture was then cooled to room temperature, and then 0.4 g of chloroplatinic acid-divinyltetramethyldisiloxane complex was added. The mixture was stirred at 50 rpm for 1.0 h at 20°C vacuum degree -90.0 kPa to obtain a silicone thermal conductive gel.
[0105] (2) Preparation of thermal conductive materials
[0106] The prepared thermally conductive gel was pressed into a sheet of a certain thickness and cured at 100° C. for 30 min to obtain a thermally conductive gasket for testing.
[0107] Example 5
[0108] (1) Preparation of silicone thermally conductive gel
[0109] Add side chain vinyl silicone oil (24.3 g) with a viscosity of 30-1000 mPa.S and a vinyl content of 0.5%, double-ended hydrogenated silicone oil (3.84 g) with a viscosity of 100-1000 mPa.S and a hydrogen content of 0.04%, single-ended hydrogenated silicone oil (102.86 g) with a viscosity of 200-1000 mPa.S and a hydrogen content of 0.003%, a macromolecular silane coupling agent represented by formula (1) (2.62 g, n is 23), aluminum oxide with a particle size of 90 μm (1425 g), aluminum oxide with a particle size of 20 μm (712.5 g), aluminum oxide with a particle size of 2 μm (712.5 g), zinc oxide with a particle size of 0.3 μm (356.6 g), ethynyl cyclohexanol (0.02 g) and a 2.0 L double planetary mixer. The mixture was heated to 100°C and stirred at 50 rpm for 2.0 h to obtain a mixture. The mixture was then cooled to room temperature, and then 0.4 g of chloroplatinic acid-divinyltetramethyldisiloxane complex was added. The mixture was stirred at 50 rpm for 1.0 h at 20°C vacuum degree -90.0 kPa to obtain a silicone thermal conductive gel.
[0110] (2) Preparation of thermal conductive materials
[0111] The prepared thermally conductive gel was pressed into a sheet of a certain thickness and cured at 100° C. for 30 min to obtain a thermally conductive gasket for testing.
[0112] Example 6
[0113] (1) Preparation of silicone thermally conductive gel
[0114] Add side chain vinyl silicone oil (53.95 g) with a viscosity of 30-1000 mPa.S and a vinyl content of 0.5%, double-end hydrogenated silicone oil (8.52 g) with a viscosity of 100-1000 mPa.S and a hydrogen content of 0.04%, single-end hydrogenated silicone oil (68.52 g) with a viscosity of 200-1000 mPa.S and a hydrogen content of 0.0098%, a macromolecular silane coupling agent represented by formula (1) (2.62 g, n is 23), aluminum oxide with a particle size of 90 μm (1425 g), aluminum oxide with a particle size of 20 μm (712.5 g), aluminum oxide with a particle size of 2 μm (712.5 g), zinc oxide with a particle size of 0.3 μm (356.6 g), ethynyl cyclohexanol (0.02 g) and a 2.0 L double planetary mixer. The mixture was heated to 100°C and stirred at 50 rpm for 2.0 h to obtain a mixture. The mixture was then cooled to room temperature, and then 0.4 g of chloroplatinic acid-divinyltetramethyldisiloxane complex was added. The mixture was stirred at 50 rpm for 1.0 h at 20°C vacuum degree -90.0 kPa to obtain a silicone thermal conductive gel.
[0115] (2) Preparation of thermal conductive materials
[0116] The prepared thermally conductive gel was pressed into a sheet of a certain thickness and cured at 100° C. for 30 min to obtain a thermally conductive gasket for testing.
[0117] Example 7
[0118] (1) Preparation of silicone thermally conductive gel
[0119] Add side chain vinyl silicone oil (40 g) with a viscosity of 30-1000 mPa.S and a vinyl content of 0.5%, double-ended hydrogenated silicone oil (6.32 g) with a viscosity of 100-1000 mPa.S and a hydrogen content of 0.04%, single-ended hydrogenated silicone oil (84.67 g) with a viscosity of 200-1000 mPa.S and a hydrogen content of 0.006%, a macromolecular silane coupling agent represented by formula (1) (2.62 g, n is 23), aluminum oxide with a particle size of 90 μm (1187.5 g), aluminum oxide with a particle size of 20 μm (593.8 g), aluminum oxide with a particle size of 2 μm (593.8 g), zinc oxide with a particle size of 0.3 μm (297.2 g), ethynyl cyclohexanol (0.02 g) and a 2.0 L double planetary mixer. The mixture was heated to 100°C and stirred at 50 rpm for 2.0 h to obtain a mixture. The mixture was then cooled to room temperature, and then 0.4 g of chloroplatinic acid-divinyltetramethyldisiloxane complex was added. The mixture was stirred at 50 rpm for 1.0 h at 20°C vacuum degree -90.0 kPa to obtain a silicone thermal conductive gel.
[0120] (2) Preparation of thermal conductive materials
[0121] The prepared thermally conductive gel was pressed into a sheet of a certain thickness and cured at 100° C. for 30 min to obtain a thermally conductive gasket for testing.
[0122] Example 8
[0123] (1) Preparation of silicone thermally conductive gel
[0124] Side chain vinyl silicone oil (40 g) with a viscosity of 30-1000 mPa.S and a vinyl content of 0.5%, double-end hydrogenated silicone oil (6.32 g) with a viscosity of 100-1000 mPa.S and a hydrogen content of 0.04%, single-end hydrogenated silicone oil (84.67 g) with a viscosity of 200-1000 mPa.S and a hydrogen content of 0.006%, macromolecular silane coupling agent (2.62 g, n is 23) represented by formula (1), aluminum oxide (1428 g) with a particle size of 90 μm, aluminum oxide (714 g) with a particle size of 20 μm, aluminum oxide (714 g) with a particle size of 2 μm, zinc oxide (357.3 g) with a particle size of 0.3 μm, ethynyl cyclohexanol (0.02 g) and a 2.0 L double planetary mixer were added. The mixture was heated to 100°C and stirred at a speed of 50 rpm for 2.0 h to obtain a mixture. The mixture was then cooled to room temperature, and then 0.4 g of chloroplatinic acid-divinyltetramethyldisiloxane complex was added, and the mixture was stirred at 50 rpm for 1.0 h at 20° C. and vacuum degree of -90.0 kPa to prepare a silicone thermal conductive gel.
[0125] (2) Preparation of thermal conductive materials
[0126] The prepared thermally conductive gel was pressed into a sheet of a certain thickness and cured at 100° C. for 30 min to obtain a thermally conductive gasket for testing.
[0127] Example 9
[0128] (1) Preparation of silicone thermally conductive gel
[0129] Add side chain vinyl silicone oil (110.73 g) with a viscosity of 30-1000 mPa.S and a vinyl content of 0.5%, double-end hydrogenated silicone oil (17.49 g) with a viscosity of 100-1000 mPa.S and a hydrogen content of 0.04%, single-end hydrogenated silicone oil (2.77 g) with a viscosity of 200-1000 mPa.S and a hydrogen content of 0.006%, a macromolecular silane coupling agent represented by formula (1) (2.62 g, n is 23), aluminum oxide with a particle size of 90 μm (1425 g), aluminum oxide with a particle size of 20 μm (712.5 g), aluminum oxide with a particle size of 2 μm (712.5 g), zinc oxide with a particle size of 0.3 μm (356.6 g), ethynyl cyclohexanol (0.02 g) and a 2.0 L double planetary mixer. The mixture was heated to 100°C and stirred at 50 rpm for 2.0 h to obtain a mixture. The mixture was then cooled to room temperature, and then 0.4 g of chloroplatinic acid-divinyltetramethyldisiloxane complex was added. The mixture was stirred at 50 rpm for 1.0 h at 20°C vacuum degree -90.0 kPa to obtain a silicone thermal conductive gel.
[0130] (2) Preparation of thermal conductive materials
[0131] The prepared thermally conductive gel was pressed into a sheet of a certain thickness and cured at 100° C. for 30 min to obtain a thermally conductive gasket for testing.
[0132] Example 10
[0133] (1) Preparation of silicone thermally conductive gel
[0134] Add side chain vinyl silicone oil (28.28 g) with a viscosity of 30-1000 mPa.S and a vinyl content of 0.5%, double-end hydrogenated silicone oil (4.47 g) with a viscosity of 100-1000 mPa.S and a hydrogen content of 0.04%, single-end hydrogenated silicone oil (98.24 g) with a viscosity of 200-1000 mPa.S and a hydrogen content of 0.006%, a macromolecular silane coupling agent represented by formula (1) (2.62 g, n is 23), aluminum oxide with a particle size of 90 μm (1425 g), aluminum oxide with a particle size of 20 μm (712.5 g), aluminum oxide with a particle size of 2 μm (712.5 g), zinc oxide with a particle size of 0.3 μm (356.6 g), ethynyl cyclohexanol (0.02 g) and a 2.0 L double planetary mixer. The mixture was heated to 100°C and stirred at 50 rpm for 2.0 h to obtain a mixture. The mixture was then cooled to room temperature, and then 0.4 g of chloroplatinic acid-divinyltetramethyldisiloxane complex was added. The mixture was stirred at 50 rpm for 1.0 h at 20°C vacuum degree -90.0 kPa to obtain a silicone thermal conductive gel.
[0135] (2) Preparation of thermal conductive materials
[0136] The prepared thermally conductive gel was pressed into a sheet of a certain thickness and cured at 100° C. for 30 min to obtain a thermally conductive gasket for testing.
[0137] Comparative Example 1
[0138] (1) Preparation of silicone thermally conductive gel
[0139] Side chain vinyl silicone oil (80 g) with a viscosity of 30-1000 mPa.S and a vinyl content of 0.5%, double-terminal hydrogen silicone oil (12.64 g) with a viscosity of 100-1000 mPa.S and a hydrogen content of 0.04%, a macromolecular silane coupling agent (3.42 g, n is 23) represented by formula (1), aluminum oxide (1024 g) with a particle size of 90 μm, aluminum oxide (512 g) with a particle size of 20 μm, aluminum oxide (512 g) with a particle size of 2 μm, zinc oxide (257.4 g) with a particle size of 0.3 μm, ethynyl cyclohexanol (0.02 g) and a 2.0 L double planetary mixer were added. The mixture was heated to 100°C and stirred at a speed of 50 rpm for 2.0 h to obtain a mixture. The mixture was then cooled to room temperature, and then chloroplatinic acid-divinyltetramethyldisiloxane complex (0.4 g) was added. The mixture was stirred at 20° C., vacuum degree -90.0 kPa, and speed of 50 rpm for 1.0 h to prepare a silicone thermally conductive gel.
[0140] (2) Preparation of thermal conductive materials
[0141] The prepared thermally conductive gel was pressed into a sheet of a certain thickness and cured at 100° C. for 30 min to obtain a thermally conductive gasket for testing.
[0142] Comparative Example 2
[0143] (1) Preparation of silicone thermally conductive gel
[0144] Side chain vinyl silicone oil (40 g) with a viscosity of 30-1000 mPa.S and a vinyl content of 0.5%, double-terminal hydrogen-containing silicone oil (4.8 g) with a viscosity of 100-1000 mPa.S and a hydrogen content of 0.04%, double-terminal hydrogen-containing silicone oil (43.6 g) with a hydrogen content of 0.013%, macromolecular silane coupling agent (1.77 g, n is 23) represented by formula (1), aluminum oxide (962 g) with a particle size of 90 μm, aluminum oxide (481 g) with a particle size of 20 μm, aluminum oxide (481 g) with a particle size of 2 μm, zinc oxide (24.01 g) with a particle size of 0.3 μm, ethynyl cyclohexanol (0.02 g) and a 2.0 L double planetary mixer were added. The mixture was heated to 100°C and stirred at a speed of 50 rpm for 2.0 h to obtain a mixture. The mixture was then cooled to room temperature, and then 0.4 g of chloroplatinic acid-divinyltetramethyldisiloxane complex was added, and the mixture was stirred at 50 rpm for 1.0 h at 20° C. and vacuum degree of -90.0 kPa to prepare a silicone thermal conductive gel.
[0145] (2) Preparation of thermal conductive materials
[0146] The prepared thermally conductive gel was pressed into a sheet of a certain thickness and cured at 100° C. for 30 min to obtain a thermally conductive gasket for testing.
[0147] Comparative Example 3
[0148] (1) Preparation of silicone thermally conductive gel
[0149] Side chain vinyl silicone oil (40 g) with a viscosity of 30-1000 mPa.S and a vinyl content of 0.5%, double-terminal hydrogen silicone oil (6.32 g) with a viscosity of 100-1000 mPa.S and a hydrogen content of 0.04%, dodecyl trimethoxysilane coupling agent (1.71 g), aluminum oxide (1425 g) with a particle size of 90 μm, aluminum oxide (712.5 g) with a particle size of 20 μm, aluminum oxide (712.5 g) with a particle size of 2 μm, zinc oxide (356.6 g) with a particle size of 0.3 μm, ethynyl cyclohexanol (0.02 g) and a 2.0 L double planetary mixer were added. The mixture was heated to 100°C and stirred at a speed of 50 rpm for 2.0 h to obtain a mixture. The mixture was then cooled to room temperature, and then chloroplatinic acid-divinyltetramethyldisiloxane complex (0.4 g) was added. The mixture was stirred at 20° C., vacuum degree -90.0 kPa, and speed of 50 rpm for 1.0 h to prepare a silicone thermally conductive gel.
[0150] (2) Preparation of thermal conductive materials
[0151] The prepared thermally conductive gel was pressed into a sheet of a certain thickness and cured at 100° C. for 30 min to obtain a thermally conductive gasket for testing.
[0152] Comparative Example 4
[0153] (1) Preparation of silicone thermally conductive gel
[0154] Side chain vinyl silicone oil (40 g) with a viscosity of 30-1000 mPa.S and a vinyl content of 0.5%, double-terminal hydrogen-containing silicone oil (6.32 g) with a viscosity of 100-1000 mPa.S and a hydrogen content of 0.04%, double-terminal hydrogen-containing silicone oil (84.67 g) with a hydrogen content of 0.006%, macromolecular silane coupling agent (2.62 g, n is 8) represented by formula (1), aluminum oxide with a particle size of 90 μm (1425 g), aluminum oxide with a particle size of 20 μm (712.5 g), aluminum oxide with a particle size of 2 μm (712.5 g), zinc oxide with a particle size of 0.3 μm (356.6 g), ethynyl cyclohexanol (0.02 g) and a 2.0 L double planetary mixer were added. The mixture was heated to 100° C. and stirred at a speed of 50 rpm for 2.0 h to obtain a mixture. The mixture was then cooled to room temperature, and then 0.4 g of chloroplatinic acid-divinyltetramethyldisiloxane complex was added, and the mixture was stirred at 50 rpm for 1.0 h at 20° C. and vacuum degree of -90.0 kPa to prepare a silicone thermal conductive gel.
[0155] (2) Preparation of thermal conductive materials
[0156] The prepared thermally conductive gel was pressed into a sheet of a certain thickness and cured at 100° C. for 30 min to obtain a thermally conductive gasket for testing.
[0157] Comparative Example 5
[0158] (1) Preparation of silicone thermally conductive gel
[0159] Side chain vinyl silicone oil (40 g) with a viscosity of 30-1000 mPa.S and a vinyl content of 0.5%, double-terminal hydrogenated silicone oil (6.32 g) with a viscosity of 100-1000 mPa.S and a hydrogen content of 0.04%, double-terminal hydrogenated silicone oil (84.67 g) with a hydrogen content of 0.006%, macromolecular silane coupling agent (2.62 g, n is 45) represented by formula (1), aluminum oxide (1425 g) with a particle size of 90 μm, aluminum oxide (712.5 g) with a particle size of 20 μm, aluminum oxide (712.5 g) with a particle size of 2 μm, zinc oxide (356.6 g) with a particle size of 0.3 μm, ethynyl cyclohexanol (0.02 g) and a 2.0 L double planetary mixer were added. The mixture was heated to 100°C and stirred at a speed of 50 rpm for 2.0 h to obtain a mixture. The mixture was then cooled to room temperature, and then 0.4 g of chloroplatinic acid-divinyltetramethyldisiloxane complex was added, and the mixture was stirred at 50 rpm for 1.0 h at 20° C. and vacuum degree of -90.0 kPa to prepare a silicone thermal conductive gel.
[0160] (2) Preparation of thermal conductive materials
[0161] The prepared thermally conductive gel was pressed into a sheet of a certain thickness and cured at 100° C. for 30 min to obtain a thermally conductive gasket for testing.
[0162] Comparative Example 6
[0163] (1) Preparation of silicone thermally conductive gel
[0164] Side chain vinyl silicone oil (17.45 g) with a viscosity of 30-1000 mPa.S and a vinyl content of 0.5%, double-terminal hydrogenated silicone oil (2.76 g) with a viscosity of 100-1000 mPa.S and a hydrogen content of 0.04%, double-terminal hydrogenated silicone oil (110.79 g) with a hydrogen content of 0.002%, macromolecular silane coupling agent (2.62 g, n is 8) represented by formula (1), aluminum oxide (1425 g) with a particle size of 90 μm, aluminum oxide (712.5 g) with a particle size of 20 μm, aluminum oxide (712.5 g) with a particle size of 2 μm, zinc oxide (356.6 g) with a particle size of 0.3 μm, ethynyl cyclohexanol (0.02 g) and a 2.0 L double planetary mixer were added. The mixture was heated to 100°C and stirred at a speed of 50 rpm for 2.0 h to obtain a mixture. The mixture was then cooled to room temperature, and then 0.4 g of chloroplatinic acid-divinyltetramethyldisiloxane complex was added, and the mixture was stirred at 50 rpm for 1.0 h at 20° C. and vacuum degree of -90.0 kPa to prepare a silicone thermal conductive gel.
[0165] (2) Preparation of thermal conductive materials
[0166] The prepared thermally conductive gel was pressed into a sheet of a certain thickness and cured at 100° C. for 30 min to obtain a thermally conductive gasket for testing.
[0167] Comparative Example 7
[0168] (1) Preparation of silicone thermally conductive gel
[0169] Side chain vinyl silicone oil (65.34 g) with a viscosity of 30-1000 mPa.S and a vinyl content of 0.5%, double-terminal hydrogenated silicone oil (10.32 g) with a viscosity of 100-1000 mPa.S and a hydrogen content of 0.04%, double-terminal hydrogenated silicone oil (55.33 g) with a hydrogen content of 0.015%, macromolecular silane coupling agent (2.62 g, n is 45) represented by formula (1), aluminum oxide (1425 g) with a particle size of 90 μm, aluminum oxide (712.5 g) with a particle size of 20 μm, aluminum oxide (712.5 g) with a particle size of 2 μm, zinc oxide (356.6 g) with a particle size of 0.3 μm, ethynyl cyclohexanol (0.02 g) and a 2.0 L double planetary mixer were added. The mixture was heated to 100°C and stirred at a speed of 50 rpm for 2.0 h to obtain a mixture. The mixture was then cooled to room temperature, and then 0.4 g of chloroplatinic acid-divinyltetramethyldisiloxane complex was added, and the mixture was stirred at 50 rpm for 1.0 h at 20° C. and vacuum degree of -90.0 kPa to prepare a silicone thermal conductive gel.
[0170] (2) Preparation of thermal conductive materials
[0171] The prepared thermally conductive gel was pressed into a sheet of a certain thickness and cured at 100° C. for 30 min to obtain a thermally conductive gasket for testing.
[0172] Comparative Example 8
[0173] (1) Preparation of silicone thermally conductive gel
[0174] Side chain vinyl silicone oil (40 g) with a viscosity of 30-1000 mPa.S and a vinyl content of 0.5%, double-end hydrogenated silicone oil (6.32 g) with a viscosity of 100-1000 mPa.S and a hydrogen content of 0.04%, single-end hydrogenated silicone oil (84.67 g) with a viscosity of 200-1000 mPa.S and a hydrogen content of 0.006%, aluminum oxide (1456 g) with a particle size of 90 μm, aluminum oxide (728 g) with a particle size of 20 μm, aluminum oxide (728 g) with a particle size of 2 μm, zinc oxide (362.8 g) with a particle size of 0.3 μm, ethynyl cyclohexanol (0.02 g) and a 2.0 L double planetary mixer were added. The mixture was heated to 100°C and stirred at a speed of 50 rpm for 2.0 h to obtain a mixture. The mixture was then cooled to room temperature, and then chloroplatinic acid-divinyltetramethyldisiloxane complex (0.3 g) was added, and the mixture was stirred at 50 rpm for 1.0 h at 20° C. and vacuum degree-90.0 kPa to prepare a silicone thermal conductive gel.
[0175] (2) Preparation of thermal conductive materials
[0176] The prepared thermally conductive gel was pressed into a sheet of a certain thickness and cured at 100° C. for 30 min to obtain a thermally conductive gasket for testing.
[0177] Performance Testing
[0178] (1) Thermal conductivity test
[0179] The thermal conductivity of the thermal conductive material was measured using a thermal conductivity tester. Before the test, the sample was made into a round block with a thickness of 6 mm and a diameter of 30 to 50 mm; the measurement was repeated three times and the average value was taken as the final result.
[0180] (2) Fatigue toughness test
[0181] The fatigue toughness of the thermal conductive material was tested using an electronic universal testing machine. Test conditions and parameters: temperature 25°C, tensile frequency 1Hz, tensile number dN (10,000 times). Test steps: (1) Cut the thermal conductive material into dumbbell-shaped strips of 50mm*10mm*1.5mm (length*width*thickness) (a style) and 50mm*10mm*1.5mm (length*width*thickness) with a 2mm wide (c) "V"-shaped notch in the middle (b style), as shown in Figure 2. Figure 1 As shown; (2) The two shapes of thermal conductive materials are respectively subjected to different strains (λ A ) was tested for 10,000 tensile cycles, and the stress-strain curve of the unnotched specimen at the 10,000th time was integrated, with the integral strain range from 1 to λ A, record the integrated area as U; check the notch expansion of the notched spline after stretching 10,000 times, record it as dc; (3) calculate the capacity release rate G according to the provided formula (I), use it as the abscissa and dc / dN as the ordinate to draw a function relationship graph. Perform linear fitting on all points whose ordinates are not 0, and the intersection of the fitting line and the X-axis is the fatigue toughness of the thermal conductive gel.
[0182] G(λ A ,N)=2k(λ A )×U(λ A ,N)×c formula (I); where,
[0183]
[0184] (3) Oil permeability test
[0185] The thermal conductive gel was cut into samples with a diameter of 3 cm and placed on filter paper with a weight of W1; the above samples were placed on a heating plate at 80°C and baked for 2 hours; after removing the thermal conductive gel sample, the filter paper was weighed, and the weight of the filter paper at this time was measured to be W2, and the oil permeability was calculated by the following formula (II).
[0186] Oil penetration rate = (W2-W1) ÷ W1 × 100% Formula (II)
[0187] The thermal conductivity test, fatigue toughness test and oil permeability test were performed on the above experimental examples, and the test results are shown in Table 1.
[0188] Table 1
[0189]
[0190]
[0191] It can be seen from the test results of Examples 1 to 10 and Table 1 that when the organic silicone thermally conductive gel includes 20-120 parts of side chain vinyl silicone oil; 1-20 parts of double-ended hydrogenated silicone oil; 2-110 parts of single-ended hydrogenated silicone oil; 2000-4000 parts of thermally conductive filler and 1-10 parts of silane coupling agent having a structure shown in formula (1); wherein the viscosity of the single-ended hydrogenated silicone oil is 20mPa.S-1000mPa.S and the hydrogen content of the hydrogenated silicone oil is 0.003%-0.0098%, the prepared organic silicone thermally conductive gel has a higher thermal conductivity and fatigue resistance after curing, and has a lower oil permeability.
[0192] The difference between Example 1, Examples 3 to 4, and Comparative Examples 4 to 5 is that the molecular weight of the silane coupling agent is different. It can be seen from the test results in Table 1 that the thermal conductivity of the thermally conductive materials prepared therefrom is greater than 7W / m·K. When the molecular weight of the silane coupling agent is low, for example, the n value in the silane coupling agent shown in formula (1) is less than 10, the oil permeability of the thermally conductive material prepared is high, and the fatigue toughness is poor; when the molecular weight of the silane coupling agent is too high, for example, the n value in the silane coupling agent shown in formula (1) is greater than 40, the oil permeability of the thermally conductive material prepared is low, but its fatigue toughness is still not ideal. When the n value in the silane coupling agent shown in formula (1) is about 23, the fatigue resistance of the prepared silicone thermally conductive gel after curing is between 1400J / m 2 Above, and the oil permeability is lower than 0.1%, with higher fatigue resistance and lower oil permeability. Good fracture toughness and resilience ensure that the material is not prone to fracture when subjected to stress, and can be completely restored to its original state, which provides a solid foundation for the material to resist fatigue failure. The n value of the silane coupling agent shown in formula (1) is less than 10, and there is a small amount of entanglement structure at the polymer / filler interface, and the polymer molecular chains are very likely to have relative slip and breakage, etc., resulting in the inability of the molecular chain to complete the retraction and the poor fatigue toughness of the material; at the same time, the low molecular weight silane coupling agent has high fluidity, resulting in a high oil overflow rate in the system. The n value of the silane coupling agent shown in formula (1) is greater than 40, and a strong entanglement structure is formed at the polymer / filler interface, resulting in brittle fracture of the material during stretching and poor fatigue toughness of the material.
[0193] By regulating the hanging chain structure in the silicone matrix and the grafted molecular chains on the filler surface, the molecular weight between the chemical cross-linking points in the silicone matrix can be extended, the polymer-filler interface layer structure can be optimized, and a silicone thermal conductive gel with a mainly physical entanglement structure can be formed. Physical entanglement can be used to dissipate energy through chain segment sliding friction and reduce viscous dissipation through mechanical interlocking, thereby achieving excellent anti-fatigue properties of the material. Even if a small amount of high molecular weight silane coupling agent remains, its interaction with the polymer matrix and filler will limit its overflow.
[0194] By comparing Example 1 with Comparative Examples 4 to 5 and Comparative Example 8, the main difference lies in whether the silane coupling agent represented by formula (1) in the present application is added. It can be seen that the silane coupling agent added in Comparative Examples 4 to 5 can improve its fatigue toughness to a certain extent, but the effect obtained is obviously not as good as the silane coupling agent added in Example 1, and has a more surprising technical effect in improving fatigue toughness.
[0195] Compared with Example 1, Example 7 and Example 8, the difference is that the number of thermally conductive fillers in the silicone thermally conductive gel is relatively small, and the number of thermally conductive fillers in Example 8 is slightly higher than the number of thermally conductive fillers in Example 1. It can be seen from the test results in Table 1 that when the proportion of thermally conductive fillers in the silicone thermally conductive gel reaches about 96%, further increasing the proportion of thermally conductive fillers will cause the thermal conductivity of the cured thermally conductive material to almost no longer increase, but its fatigue resistance will drop sharply. Reducing the number of thermally conductive fillers in the silicone thermally conductive gel is beneficial to improving the fatigue resistance of the cured thermally conductive material, but too little thermally conductive fillers in the silicone thermally conductive gel will cause its thermal conductivity to be greatly reduced. Good fracture toughness and resilience ensure that the material is not prone to fracture and damage when subjected to stress, and can be fully restored to its original state, which provides a solid foundation for the material to resist fatigue failure.
[0196] If the amount of thermal conductive filler is too high, the material's stretchability will be sacrificed, thereby sacrificing the material's fatigue performance. Reducing the filler content of the system to a certain extent can improve the material's stretchability without sacrificing too much strength, so the material's fatigue performance can be improved. However, when the filler content is too low, its role in linking the suspension chain is sacrificed, making the material very easy to break when stressed, thereby sacrificing the material's fatigue performance. The reduction in filler content will significantly affect the construction of the thermal conductive path in the material, so the thermal conductivity will be greatly reduced.
[0197] Compared with Example 1, Example 9 and Example 10, the difference lies in that the mass ratio of single-ended hydrogenated silicone oil to total silicone oil (that is, the sum of the masses of single-ended hydrogenated silicone oil, double-ended hydrogenated silicone oil and side chain vinyl silicone oil) is different. It can be seen from the test results in Table 1 that when the total silicone oil remains basically unchanged, as the mass fraction of the added single-ended hydrogenated silicone oil increases, the fatigue toughness of the cured thermal conductive material shows a trend of first increasing and then decreasing. When the mass fraction of the single-ended hydrogenated silicone oil added is about 84 parts, its fatigue toughness is relatively high.
[0198] according to model, the distance between chemical crosslinks and the molecular weight of the dangling chains jointly affect the fatigue properties.
[0199] where Ni is the number of Kuhn monomers per chain, ni is the number of molecular chains per unit volume, bi and Ui are the length and breakage energy of the Kuhn monomer on the i-th polymer chain, respectively.
[0200] Properly increase the mass fraction of single-end hydrogen-containing silicone oil, the molecular weight of the larger hanging chain can increase the distance between chemical crosslinking points, thereby synergistically improving the fatigue performance of the material. However, when the mass fraction of single-end hydrogen-containing silicone oil is too high, the molecular weight of the single-end hydrogen-containing silicone oil is smaller than the molecular weight between chemical crosslinking points, thereby sacrificing the fatigue performance of the material.
[0201] Compared with Example 1, Comparative Example 6 and Comparative Example 7, the difference lies in the different mass ratios of the single-end hydrogenated silicone oil to the total silicone oil (i.e., the sum of the mass of the single-end hydrogenated silicone oil, the double-end hydrogenated silicone oil and the side-chain vinyl silicone oil) and the different hydrogen contents of the single-end hydrogenated silicone oil. It can be seen from the test results in Table 1 that when the total silicone oil remains basically unchanged, when the hydrogen content of the single-end hydrogenated silicone oil is too high, for example, when the hydrogen content of the single-end hydrogenated silicone oil is greater than 0.01%, the obtained organic silicone thermal conductive gel has poor fatigue resistance after curing and a high oil permeability. When the hydrogen content of the single-end hydrogenated silicone oil is too low, for example, when the hydrogen content of the single-end hydrogenated silicone oil is less than 0.003%, the obtained organic silicone thermal conductive gel has poor fatigue resistance after curing and a high oil permeability.
[0202] Good fracture toughness and resilience ensure that the material is not prone to fracture when subjected to stress and can fully recover to its original state, which provides a solid foundation for the material to resist fatigue failure. When the hydrogen content of the single-ended hydrogenated silicone oil is too low, the "quasi-cross-linking" self-entanglement effect produced by the silicone resin matrix causes brittle fracture of the material during stretching and poor fatigue toughness of the material. When the hydrogen content of the single-ended hydrogenated silicone oil is too high, according to The model introduces a lower molecular weight of the hanging chain to obtain a high molecular weight between the chemical cross-linking points, sacrificing the synergistic effect between the two, resulting in extremely poor fatigue toughness of the material; at the same time, the low molecular weight silane coupling agent has high fluidity, resulting in a high oil overflow rate of the system.
[0203] The technical solutions provided by the embodiments of the present application are introduced in detail above. Specific examples are used herein to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the method of the present application and its core idea. At the same time, for technical personnel in this field, according to the idea of the present application, there will be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as a limitation on the present application.
Claims
1. A silicone thermally conductive gel, characterized in that: By mass, the organic silicone thermal conductive gel comprises 20-120 parts of side chain vinyl silicone oil; 1-20 parts of double-ended hydrogenated silicone oil; 2-110 parts of single-ended hydrogenated silicone oil; 2000-4000 parts of thermal conductive filler and 1-10 parts of silane coupling agent; wherein the viscosity of the single-ended hydrogenated silicone oil is 200mPa.S-1000mPa.S, the hydrogen content of the single-ended hydrogenated silicone oil is 0.003%-0.0098%, and the molecular formula of the silane coupling agent is shown in the following formula (1): Among them, 12≤n≤40.
2. The thermally conductive silicone gel according to claim 1, characterized in that: 20≤n≤25; and / or The hydrogen content of the single-ended hydrogenated silicone oil is 0.003%-0.008%; and / or The mass fraction of the thermally conductive filler in the thermally conductive silicone gel is 3000 parts to 3600 parts; and / or The organic silicon thermally conductive gel also includes 0.1 to 1 part of a catalyst; and / or The organic silicon thermally conductive gel further comprises 0.01 to 0.5 parts of an inhibitor.
3. The thermally conductive silicone gel according to claim 1, characterized in that: The viscosity of the side chain vinyl silicone oil is 30-1000 mPa.S; and / or The vinyl content of the side chain vinyl silicone oil is 0.2%-1%; and / or The viscosity of the double-ended hydrogen-containing silicone oil is 100-1000 mPa.S; and / or The hydrogen content of the double-ended hydrogen-containing silicone oil is 0.02%-0.08%; and / or The average particle size of the thermally conductive filler is 0.1 μm-100 μm; and / or The thermally conductive filler is selected from one or more of aluminum oxide, aluminum nitride, zinc oxide, boron nitride and diamond.
4. The thermally conductive silicone gel according to claim 2, characterized in that: The catalyst comprises at least one of chloroplatinic acid, chloroplatinic acid-isopropanol complex, and chloroplatinic acid-divinyltetramethyldisiloxane complex; and / or The inhibitor includes at least one of ethynyl cyclohexanol, 2-phenyl-3-butyn-2-ol, 2-methyl-3-butyn-2-ol, 3-methyl-1-ethynyl-3-ol, 3,5-dimethyl-1-ethynyl-3-ol, and 3-methyl-1-dodecyn-3-ol.
5. The thermally conductive silicone gel according to claim 3, characterized in that: The thermally conductive filler includes a first filler, a second filler, a third filler and a fourth filler. The average particle size of the first filler is 85μm-95μm, and the mass fraction of the first filler is 1000 to 1500 parts; the average particle size of the second filler is 10μm-30μm, and the mass fraction of the second filler is 500 to 800 parts; the average particle size of the third filler is 1μm-5μm, and the mass fraction of the third filler is 500 to 800 parts; the average particle size of the fourth filler is 0.1μm-0.5μm, and the mass fraction of the fourth filler is 200 to 400 parts.
6. The thermally conductive silicone gel according to any one of claims 1 to 5, characterized in that: The hydrogen content of the single-end hydrogen-containing silicone oil is less than one twenty-seventh of the vinyl content of the side-chain vinyl silicone oil.
7. A method for preparing the thermally conductive silicone gel according to any one of claims 1 to 6, characterized in that: The following steps are involved: The side chain vinyl silicone oil, double-end hydrogen-containing silicone oil, single-end hydrogen-containing silicone oil, silane coupling agent represented by formula (1) and thermal conductive filler are mixed according to a proportion to obtain the silicone thermal conductive gel.
8. A thermally conductive material, characterized in that: The thermally conductive material is prepared by curing the thermally conductive silicone gel according to any one of claims 1 to 6.
9. The thermally conductive material according to claim 8, characterized in that The curing temperature of the silicone thermally conductive gel is 100° C. to 150° C., and the curing reaction time is 20 min to 40 min; and / or The thermal conductivity of the thermally conductive material is greater than 4.0 W / mK; and / or The oil permeability of the thermally conductive material is ≤1%; and / or The fatigue toughness of the thermal conductive material is greater than 900 J·m -2 .
10. The organic silicon thermally conductive gel according to any one of claims 1 to 6 or the thermally conductive material according to claim 8 or 9 is used in an optical module.